PENGARUH CAMPURAN SEMEN-LEMPUNG TERHADAP PENURUNAN KADAR LOGAM DALAM LINDI DARI TPA BENOWO KOTA SURABAYA - Didik Sarudji (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2006)
Leachate is a problem in solid waste final disposal. Leachate potentially causes environmental problems that influence human health after reaching top food chain. In the human body heavy metals are accumulated, and in a certain concentration could interfere central nervous system. The aim of this laboratory study was to investigate how far the mixtures of cement and clay could reduce effectively metal concentrations in leachate from Benowo solid waste disposal site. The method included treating the mixture of cement and clay in several ratios to leachate samples in the jar-test. After mixing, the precipitate was separated from the supernatant. The metal contents in the supernatant were analyzed in Balai Laboratorium Kesehatan Surabaya. The results showed that the mixtures could reduce, even eliminate, Fe, Mn, Zn, Cd and Pb in the leachate.